THE INFLUENCE OF INTERACTION ORIENTATION ON BEHAVIORAL INTENTIONS ON JAPANESE RESTAURANTS IN JAKARTA AND TANGERANG - Indry Pradipta (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The restaurant business in Indonesia is a promising business in line with the increasing number of middle class in Indonesia. The number of restaurants in Indonesia in 2010 - 2015 is also increased. This study has a purpose to know the relation between interaction orientation, customer satisfaction, behavioral intention, trust, and commitment variables at Japanese restaurants. The data of this study were collected from 200 respondents who have eaten at XYZ Japanese restaurant in Jakarta or Tangerang area within the last three months. Using Likert five points scale, the sample design used in this study is non-probability sampling with a convenience sampling technique. The variables were then analyzed using Structural Equation Modeling with the help of the Analysis of Moment Structures program version 21.0. The results of this study suggest that interaction orientation has a direct positive and significant effect on customer satisfaction. Customer satisfaction has an immediate positive and significant impact to trust, commitment, and behavioral intention, and engagement has a direct positive and significant effect on the behavioral plan.